Creators' income situation in the digital age - Alexander Cuntz (Luxembourg Income Study (LIS), 2018)
The digital transformation imposes both opportunities and risks for creativity and for creative employment, with implications for trends in income levels and the distribution of income. First, we consider skill-biased technological change as a determinant of income and labor market outcomes in the arts. Arguably, the IT revolution has changed the demand for certain skills, with creative occupations being more in demand than general employment. Second, we consider declines in the costs of generating new works and artistic experimentation due to digital technologies, and their effect on the barriers to entry in labor markets. Third, we touch upon the rise of online contract labor in certain creative professions as a determinant of income. Here, online platforms can change creators' access to work opportunities and it may alter the way income is distributed. We find that wage trends for creative workers in the digital age outperform general trends in the population: based on various data sources and various ways to identify creators, we see creators losing less or even gaining a better income position in relative terms. From a policy perspective, results do not lend support to the idea that creators' income situation has systematically worsened with the rise of the internet and its intermediaries. Evidence on changing distributions of income is ambiguous as trends differ from one country to the next.
Keywords: J24; J28; J31; L82; O15; O33; O34; Z10; 330; creative economy; artist; creativity; occupation; labor market; self-employment; income; wages; distribution; skill biased technological change; digital technology; internet